2017
DOI: 10.1002/cncr.30959
|View full text |Cite
|
Sign up to set email alerts
|

Treatment decisions and employment of breast cancer patients: Results of a population‐based survey

Abstract: Background Many patients with breast cancer work for pay at time of diagnosis, and the treatment plan may threaten their livelihood. Understanding work experiences in a contemporary population-based sample is necessary to inform initiatives to reduce the burden of cancer care. Methods We surveyed women aged 20–79 years diagnosed with stages 0–II breast cancer as reported to the Georgia and Los Angeles SEER registries in 2014–15. Of 3672 eligible women, 2502 responded (68%); we analyzed 1006 who reported work… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
45
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 58 publications
(49 citation statements)
references
References 25 publications
2
45
0
2
Order By: Relevance
“…The distinction between BCSs who underwent surgery and who do not mean those who have advanced stage or not, because, except for stage IV where distant metastasis is apparent, almost all BCSs experience surgery in general. Previous studies reported that breast cancer surgery was associated with SL lasting 1 month or longer (39,40), while median duration of hospitalization among BCSs were reported to be about 6.79-10.37 days in Japan (41). Surgical treatment may result in challenging sequelae including scar pain and reduced range of motion, particularly in the arm and chest region, fatigue, and lymphedema; these symptoms increase the time to RTW and are related to unemployment(41).…”
Section: Resultsmentioning
confidence: 99%
“…The distinction between BCSs who underwent surgery and who do not mean those who have advanced stage or not, because, except for stage IV where distant metastasis is apparent, almost all BCSs experience surgery in general. Previous studies reported that breast cancer surgery was associated with SL lasting 1 month or longer (39,40), while median duration of hospitalization among BCSs were reported to be about 6.79-10.37 days in Japan (41). Surgical treatment may result in challenging sequelae including scar pain and reduced range of motion, particularly in the arm and chest region, fatigue, and lymphedema; these symptoms increase the time to RTW and are related to unemployment(41).…”
Section: Resultsmentioning
confidence: 99%
“…The distinction between BCSs who underwent surgery and who do not mean those who have advanced stage or not, because, except for stage IV where distant metastasis is apparent, almost all BCSs experience surgery in general. Previous studies reported that breast cancer surgery was associated with SL lasting 1 month or longer [42,43], while median duration of hospitalization among BCSs were reported to be about 6.79-10.37 days in Japan [44]. Surgical treatment may result in challenging sequelae including scar pain and reduced range of motion, particularly in the arm and chest region, fatigue, and lymphedema; these symptoms increase the time to RTW and are related to unemployment [44].…”
Section: Discussionmentioning
confidence: 99%
“…The distinction between BCSs who undergo surgery and those who do not suggests a relation to cancer stage (early or advanced) because almost all BCSs undergo surgery, except for those with stage IV cancer, in which distant metastasis is apparent. Previous studies have reported that breast cancer surgery is associated with SL lasting 1 month or longer [42,43], and that the median duration of hospitalization among BCSs in Japan is about 6.79-10.37 days [44]. Surgical treatment may result in challenging sequelae, including scar pain, fatigue, lymphedema, and reduced range of motion, particularly in the arm and chest region; these symptoms increase the time to RTW and are related to unemployment [45].…”
Section: Discussionmentioning
confidence: 99%